THE FACTOR OF STUDENTS’ PROBLEM IN WRITING RECOUNT TEXT OF EIGHTH GRADE AT SMP NEGERI 12 KOTABUMI ACADEMIC YEAR 2022/2023 - Rulik Setiani; Mutia Restika; Rini Susilowati (Language and Education Journal, 2023)
The aim of this study was to determine the factors causing students’ problems in writing recount text and what is the most dominant factor toward students’ problems in writing recount text of eight grade at SMP Negeri 12 Kotabumi Academic Year 2022/2023. This study uses a descriptive-qualitative method with document as a data collection technique which examined students’ writing recount text of 27 students by taking 6 students’ writing recount text from students who have the lowest score. The research finding show that the students have a problem in linguistic problems: grammar 23 errors, vocabulary 2 errors, and choice of sentence no error, in cognitive problems: punctuation 18 errors, capitalization 4 errors, spelling 5 errors, and paragraphing 1 error. Hence, reading a lot before writing becomes one’s solution to eliminates students’ difficulties in writing text. It is recommended for students to read more and practice how to write good text especially in writing recount text. Students must understand well the components in writing a good paragraph, so that the students do not experience problems during the process. In addition, they must also pay more attention to the teacher’s explanation when the teaching and learning process is carried out.